2015
DOI: 10.1542/peds.2015-0414
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Consequences of the Detection of Fragile X Carriers in Newborn Screening

Abstract: The possibility of newborn screening for fragile X syndrome is complicated by the potential for identifying premutation carriers. Although knowing the child's carrier status has potential benefits, the possibility of late-onset disorders in carrier children and their parents raises concerns about whether such information would be distressing to parents and potentially more harmful than helpful. This study sought to answer this question by offering voluntary fragile X screening to new parents and returning resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 41 publications
(40 reference statements)
0
24
0
Order By: Relevance
“…Third, there may be family characteristics that we did not assess that could have contributed to parents' willingness to have their baby screened, and the parents who agreed to participate in the longitudinal study may be different from those who did not (although we found no differences in maternal age, marital status, race/ ethnicity, maternal education, and CGG repeat length of the identified child). 60 Finally, the study was not designed to prove benefit for children and, as such, does not answer the ultimate question of whether FX NBS is good public policy.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there may be family characteristics that we did not assess that could have contributed to parents' willingness to have their baby screened, and the parents who agreed to participate in the longitudinal study may be different from those who did not (although we found no differences in maternal age, marital status, race/ ethnicity, maternal education, and CGG repeat length of the identified child). 60 Finally, the study was not designed to prove benefit for children and, as such, does not answer the ultimate question of whether FX NBS is good public policy.…”
Section: Discussionmentioning
confidence: 99%
“…[69][70][71][72] Similarly, most studies of newborn screening report minimal psychological distress for parents after early diagnosis. 68,73,74 However, there are still concerns about the psychological impact on parents who receive results from pediatric predictive testing, 75 and additional research should be focused on identifying and assisting those parents who may be more vulnerable to adverse outcomes after receiving results. 74,76 Furthermore, additional research and supports need to address the challenge of managing the child's condition, 73 impact on family dynamics, 77 potential for discrimination and stigma, 78 and ever-changing societal perceptions.…”
Section: Clinical and Ethical Implications Of Early Detectionmentioning
confidence: 99%
“…68,73,74 However, there are still concerns about the psychological impact on parents who receive results from pediatric predictive testing, 75 and additional research should be focused on identifying and assisting those parents who may be more vulnerable to adverse outcomes after receiving results. 74,76 Furthermore, additional research and supports need to address the challenge of managing the child's condition, 73 impact on family dynamics, 77 potential for discrimination and stigma, 78 and ever-changing societal perceptions. 79 Although considerable work lies ahead of the autism field, the development and validation of biomarkers for ASD will help move the field of psychiatry toward its aspiration of precision medicine, 80 in order to determine the best treatment, at the optimal time, for specific subtypes.…”
Section: Clinical and Ethical Implications Of Early Detectionmentioning
confidence: 99%
“…Wafer bonding adds additional level of complexity in the process, and affects the alignment accuracy depending on the type of bonding used [19]. Unless some special self-aligning device designs [20] or pattern distortion compensation methods are adapted, integration precision usually only relies on a high density of alignment marks near device structures. Better understanding of the wafer-scale non-uniformities of the bonded III-V on Si wafers is therefore needed for the design and processing optimization.…”
Section: Introductionmentioning
confidence: 99%